INFORMATIVE AND FORMAL DESCRIPTION OF STRUCTURE DYNAMICS CONTROL TASK OF CYBER-PHISICAL SYSTEMS - Sokolov, Boris; Potryasaev, Semen; Serova, Elena; Ipatov, Yury; Andrianov, Yury (Journal of Applied Engineering Science, 2019)
The authors propose the informative and formal description of Structure Dynamics Control Task of Cyber-physical Systems (CPS). The main advantage of proposed poly-model multicriterion approach for the structure dynamics control tasks decision  is that, in comparison with previously developed control models oriented on CPS simulation, proposed models allow to increase the efficiency, validity and, in general, the quality of the SD control CPS due to the original combination of their static and dynamic models.
Keywords: integrated modelling and simulation; structure dynamics control; cyber-physical systems